(untitled) (Journal of Asian Development Studies, 2024)
In recent years, noise pollution in urban zones has reached critical levels, primarily driven by increased road traffic and poor urban planning. This research is crucial as it quantifies noise pollution in different urban settings of Peshawar, Pakistan, providing valuable insights into the severity of the issue. By using noise descriptors such as Leq-24h, L1, L10, L50, L90, L99, Lmax, Lmin, LNP, and NC. A comparison with the Pak-NEQS 2010 standards revealed that during the daytime, 100% of silence zones, 91% of commercial areas, and 90% of residential areas exceeded the permissible noise limits. Similarly, nighttime measurements showed that 83% of silence zones, 87% of commercial areas, and 90% of residential areas were also above the acceptable limits. Strong correlations between Leq and other noise descriptors were observed, and land use characteristics significantly impacted noise levels during the day. This data highlights the urgent need for regulatory measures to mitigate the growing issue of noise pollution in urban environments.